Tautomeric photoswitches: anion-assisted azo/azine-to-hydrazone photochromism. Issue 28 (21st May 2019) - Filo, Juraj; Tisovský, Pavol; Csicsai, Klaudia; Donovalová, Jana; Gáplovský, Martin; Gáplovský, Anton; Cigáň, Marek
Abstract : The photoswitching behaviour of isatin 4-nitrophenylhydrazones in presence of anions was investigated. Abstract : The photoswitching properties of two easily synthesized isatin 4-nitrophenylhydrazones were investigated. Although the parent isatin 4-nitrophenylhydrazones exhibit low addressability which hampers their photochromic applications, the addition of strongly basic anions to phenylhydrazone solutions creates a new Vis–Vis photochromic system with the unusual azo/azine-to-hydrazone photo-tautomerization process as the photoswitching mechanism. To the best of our knowledge, this is the first report related to the anion-assisted azo/azine-to-hydrazone photo-tautomerism.